Marion Butler and American Populism - Hunt, James L. (James Logan), 1959- (University of North Carolina Press, 2003)
Exploring the life and leadership of Marion Butler, James Hunt offers insight into the challenge of American reform politics. He served in the US Senate and was a crucial figure in the Populist Party. In this account, Hunt seeks to show how strongly Butler believed in Populist principles.
Keywords: Butler, Marion, -- 1863-1938.; United States. -- Congress. -- Senate -- Biography.; États-Unis. -- Congress. -- Senate -- Biographies.; Butler, Marion, -- 1863-1938; United States. -- Congress. -- Senate; Butler, Marion.; Legislators -- United States -- Biography.; Politicians -- North Carolina -- Biography.; Populism -- North Carolina -- History.; North Carolina -- Politics and government -- 1865-1950.; Electronic books.; Parlementaires -- États-Unis -- Biographies.; Politiciens -- Caroline du Nord -- Biographies.; Populisme -- Caroline du Nord -- Histoire.; Caroline du Nord -- Politique et gouvernement -- 1865-1950.; Livres numériques.; e-books.; BIOGRAPHY & AUTOBIOGRAPHY -- Political.; POLITICAL SCIENCE -- Government -- Legislative Branch.; Legislators; Politics and government; Politicians; Populism; North Carolina; United States; Populismus; Politici.; Populisme.; 1865-1950; Biography; Biographies; History; Biografieën (vorm); Biographies.